```--   To proof the monad laws, we have to proof the laws depending for both 'lazyEval' and 'smallStep'.
--   First for 'lazyEval':
--
--   > (1) lazyEval (return a >>= k)
--   >     ==  lazyEval (Pending (Cont (Bind k) TransNone TransNone Root) (Final a))
--   >     ==  evalStack (Cont (Bind k) TransNone TransNone Root) (lazyEval (Final a))
--   >     ==  evalStack (Cont (Bind k) TransNone TransNone Root) a
--   >     ==  evalStack Root \$ lazyEval \$ k a
--   >     ==  lazyEval (k a)
--   >
--   > (2) lazyEval (m >>= return)
--   >     ==  lazyEval (Pending (Cont (Bind Final) TransNone TransNone Root) m)
--   >     ==  evalStack (Cont (Bind Final) TransNone TransNone Root) (lazyEval m)
--   >     ==  evalStack Root \$ lazyEval \$ Final \$ lazyEval m
--   >     ==  lazyEval m
--   >
--   > (3) lazyEval (m >>= (\x -> k x >>= h))
--   >     ==  lazyEval (Pending (Cont (Bind (\x -> Pending (Cont (Bind h) TransNone TransNone Root) (k x))) TransNone TransNone Root) m)
--   >     ==  evalStack (Cont (Bind (\x -> Pending (Cont (Bind h) TransNone TransNone Root) (k x))) TransNone TransNone Root) (lazyEval m)
--   >     ==  evalStack Root \$ lazyEval \$ (\x -> Pending (Cont (Bind h) TransNone TransNone Root) (k x)) (lazyEval m)
--   >     ==  evalStack Root \$ lazyEval \$ Pending (Cont (Bind h) TransNone TransNone Root) \$ k \$ lazyEval m
--   >     ==  lazyEval (Pending (Cont (Bind h) TransNone TransNone Root) (Pending (Cont (Bind k) TransNone TransNone Root) m))
--   >     ==  lazyEval ((m >>= k) >>= h)
--
--   Now for 'smallStep':
--   > (1) smallStep (return a >>= k)
--   >     ==  smallStepPending (Pending (Cont (Bind k) TransNone TransNone Root) (Final a))
--   >     ==  smallStep \$ Pending (pushCoder TransNone Root) (k a)
--   >     ==  smallStepPending \$ Pending Root (k a)
--   >     ==  smallStep (k a)
--   >
--   > (2) smallStep (m >>= return)
--   >     ==  smallStepPending (Pending (Cont (Bind Final) TransNone TransNone Root) m)
--   >     ==  smallStepPending Root m
--   >     ==  smallStep m
--   >     use induction on the length of step-sequences
--   >     use case distinction on what steps are produced
--   > (3) tbd
--
--   Todo: proof that if strictEval m == v then lazyEval m == v
--   Todo: proof that if only the bind and return combinators are used, that
--         lazyEval m == runIdentity m
--   Todo: proof mfix laws.